Immigrants, voter sentiment, and local public goods: The case of museums. (7th May 2021) - Dalle Nogare, Chiara; Scuderi, Raffaele; Bertacchini, Enrico
Abstract: We present a model where museum commitment to immigrant integration is conditioned by the possible negative reactions of native visitors and patrons. We then exploit the rich information provided by the 2015 Italian museum census to investigate the factors associated with a higher probability of museums developing promotion programmes targeting an immigrant audience, with a special focus on the size of immigrant communities and the importance of anti‐immigrant sentiment in the local context. We proxy the latter with the municipal vote shares of parties with an anti‐immigrant agenda in the 2013 national elections. Our evidence shows that the vote share of Lega Nord has a significantly negative and sizable estimated coefficient. Conversely, we find no positive association with the overall share of immigrants—only the size of specific minorities at the local level increases the likelihood that a museum engages immigrants. We control for a number of context variables and specific museum characteristics, some of which (age of establishment, type of collection) show a positive association with museum commitment to immigrant integration.